HUBUNGAN ANTARA KEPUASAN KERJA DAN KOMITMEN ORGANISASI PADA DOSEN DAN TENAGA KEPENDIDIKAN DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Fendi Ntobuo; Rahmatia Misda S. Keki (program studi psikologi, 2022)
This research aims to determine the relationship between job satisfaction and organizational commitment of lecturers and education staff at the Muhammadiyah University of Gorontalo. The research uses a correlational design using a quantitative approach. The sampling technique used a random sampling technique with a total sample of 70 respondents. Hypothesis testing using Pearson product moment correlation analysis. The results indicated, there is a positive relationship between job satisfaction and organizational commitment at the Muhammadiyah University of Gorontalo with the result that p = 0.000 is smaller than α = 0.05, which means that the higher the job satisfaction, the higher also the organizational commitment.